Frequency of overweight/obesity among a group of children with celiac disease in Iran - Shahraki, Touran; Shahraki, Mansour; Hill, Ivor D. (Gastroenterology Review/Przegląd Gastroenterologiczny, 2018)
Introduction : A small number of overweight and obese children with celiac disease (CD) has been reported. Aim : To estimate the prevalence of obesity, underweight and normal weight in a group of Iranian pediatric patients. Material and methods : In a retrospective study from 2007 to 2015, 225 children less than 18 years old with biopsy-proven CD were enrolled. Data collected included demographic characteristics, clinical presentation, antibody titers and severity of small-bowel mucosal damage. Body mass index (BMI) profile of subjects was calculated based on the age and gender percentile at presentation. Results : The mean ± standard deviation (SD) for age was 7.4 ±3.8 and 62% of patients were female. Fifty-four percent of patients presented with a normal BMI, 43% were underweight, and the remaining patients (3.5%) were overweight/obese. The mean age of underweight and normal weight patients was higher than that of obese/overweight patients. Mean ± SD of TTG titer was higher in overweight/obese and normal weight children compared to underweight subjects. The majority of patients (195/225) had severe enteropathy compatible with Marsh III on duodenal biopsy. Most of the children had gastrointestinal (GI) and extra-intestinal manifestations on presentation. There was no association between severity of histological disease and BMI for age. Five out of eight cases in the obese/overweight group had an index case with CD in their family. Conclusions : This study highlights the importance of considering celiac disease in children regardless of their BMI. Failure to diagnose CD in children leads to unnecessary diagnostic delays and long-term adverse health consequences.